Conscientiousness and Openness as Predicators of Risk and Delinquent Behaviour of Adolescents - Krstić, Miroslav Ž.; Ristić, Bojana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
The authors intended to single out some predicators of risk and delinquent behaviour of adolescents aiming to take various preventive activities, particularly in the sphere of the behavioural disorders of children and the young. For the purpose of this paper, the authors used the Questionnaire for Risk and Delinquent Behaviour of the Young, the Scales of Risk Behaviour—both of a recent date—and the Questionnaires of Dimensions/Characteristics of Personalities of Five-Factor and Six-Factor Personality Models, following some of demographic data, on the basis of assessment of family relationships, level of emotional and social intelligence of the examinees and other parameters. The intention was to use the reviews of four specific studies referenced in the paper to make practical and theoretical contribution, primarily in psycho-diagnostics, forensic psychology, psychology of mental health of children and the young in prediction of their behaviour. The contribution will be useful for psychology and science in general, because the prediction is one of the most important objectives of science. In this paper, due to the size limitations, the authors will deal with only the study entitled “The Structure of Personality and Risk Factors with Adolescents” with a suggestion of practical application in clinical psychology and applied branches of clinical psychology. The objective of the research was to question whether the personal traits are statistically significant predicators of risk and delinquent behaviour of adolescents. Besides the research of the predicative influence, the differences in the relationship to socio-demographic traits of adolescents were investigated as well. One hundred thirty-five high school students participated in the investigation. The dimensions of the personality were investigated using the Big Five Inventory (BFI), while the risk and delinquent behaviours were investigated using the 2007 questionnaire SRDP. The results show that the dimensions of conscientiousness and openness represent the predicators of various categories of risk and delinquent behaviour.